Pengaruh Pembiasaan Shalat Dhuha Berjamaah Terhadap Kesalehan Sosial Siswa Kelas VII SMP Muhammadiyah 10 Bandung - Dayat Indra Hidayat; Ahmad Syauqy Ridha (CV Putra Publisher, 2023)
The purpose of this research is that the writer intends to find out the effect of the habituation of the Duha prayer in congregation on the social piety of class VII students at SMP Muhammadiyah 10 Bandung. This research is motivated by the idea that the habit of praying dhuha in congregation can affect social piety. Therefore the hypothesis put forward is that the higher the habit of praying dhuha in congregation, the higher the social piety. The method used is descriptive correlational method. As for data collection techniques using observation, questionnaires, interviews, documentation, and literature study. Then to analyze the data using a statistical approach.